Climate change anxiety in China, India, Japan, and the United States. (May 2023) - Tam, Kim-Pong; Chan, Hoi-Wing; Clayton, Susan
Abstract: Climate change anxiety is becoming recognized as a way in which climate change affects mental health. It is not only observed in populations that suffer the most from the direct impacts of climate change but also can be trigged by the mere thought and perception about such impacts. Although climate change is a global problem that is a cause for concern around the world, research on climate anxiety has only recently utilized validated measures, and it has mostly been conducted in Western and developed societies. In response to this research gap, we conducted a cross-national study of climate change anxiety using the Climate Change Anxiety Scale, with participants (N = 4000) from four of the top emitters in the world (China, India, Japan, and the U.S.) which vary in their climate change vulnerabilities and resilience. We demonstrated that the widely adopted measure of climate change anxiety exhibited configural and metric invariance in the four countries. Climate change anxiety was apparently higher in the Chinese and Indian populations than in the Japanese and American populations. There were some demographic correlates of climate change anxiety, but the pattern was not always consistent across the countries. Climate change anxiety was positively associated with engagement in climate action in all four countries, but apparently more so for sustainable diet and climate activism than resource conservation and support for climate policy. The effect was driven more robustly by the cognitive-emotional impairment dimension than the functional impairment dimension of climate change anxiety. Taken together, these observations suggest that the Climate Change Anxiety Scale can be used to assess climate change anxiety across countries, and that there are both similarities and variations across different societal contexts with respect to the experience of climate change anxiety. Future research must take these complexities into consideration. Highlights: We examined climate change anxiety in four of the top emitters in the world: China, India, Japan, and the U.S. We demonstrated configural and metric invariance of the Climate Change Anxiety Scale across the countries Climate change anxiety was apparently higher in the Chinese and Indian samples than among the Japanese and American participants There were some demographic correlates of climate change anxiety, but the pattern was not always consistent across the countries Climate change anxiety was associated with climate action; this effect was driven more robustly by cognitive-emotional impairment than functional impairment